Antiprotozoal Sesquiterpene Pyridine Alkaloids from Maytenus ilicifolia - Santos, Vania A. F. F. M. [UNESP]; Regasini, Luis O. [UNESP]; Nogueira, Claudio R. [UNESP]; Passerini, Gabriela D. [UNESP]; Martinez, Isabel [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Graminha, Márcia Aparecida Silva [UNESP]; Cicarelli, Regina Maria Barreto [UNESP]; Furlan, Maysa [UNESP] (Amer Chemical Soc, 2012)
As part of a bioprospecting program aimed at the discovery of antiprotozoal agents from the Brazilian flora, two new sesquiterpene pyridine alkaloids, ilicifoliunines A (1) and B (2), along with the known alkaloids aquifoliunine E-I (3) and mayteine (4), were isolated from the root bark of Maytenus ilicifolia. The structures of 1 and 2 were established on the basis of spectroscopic data interpretation. Alkaloid 3 displayed potent in vitro antiprotozoal activity against Leishmania chagasi and Trypanosoma cruzi, with IC50 values of 1.4 and 41.9 mu M, respectively, as well as low cytotoxicity against murine peritoneal macrophages (IC50 of 1.8 mM).